Prevalence and covariates of abnormal left ventricular geometry in never-treated hypertensive patients in Tanzania. (February 2014) - Chillo, Pilly; Lwakatare, Johnson; Rieck, Åshild E.; Lutale, Janet; Gerdts, Eva
Abstract Aim. To assess prevalence, type and covariates of abnormal left ventricular (LV) geometry in untreated native Tanzanian patients with hypertension in relation to normotensive controls. Methods. Echocardiography was performed in 161 untreated hypertensive outpatients and 80 normotensive controls at a tertiary hospital in Tanzania. Hypertensive heart disease was defined as presence of increased LV mass or relative wall thickness (RWT). Results. The prevalence of hypertensive heart disease increased with the severity of hypertension and was on average 62.1% among patients and 12.5% in controls. In multivariate analyses, higher LV mass index was associated with higher systolic blood pressure (β = 0.28), body mass index (β = 0.20), peak early transmitral to medial mitral annulus velocity ratio (β = 0.16), and with lower stress-corrected midwall shortening (scMWS) (β = − 0.44) and estimated glomerular filtration rate (β = − 0.16), all p < 0.05. Higher RWT was associated with higher systolic blood pressure (β = 0.16), longer E-wave deceleration time (β = 0.23) and lower scMWS (β = − 0.66), irrespective of LV mass (all p < 0.05). Conclusion. Subclinical hypertensive heart disease is highly prevalent in untreated native hypertensive Tanzanians and associated with both systolic and diastolic LV dysfunction. Management of hypertension in Africans should include high focus on subclinical hypertensive heart disease.